Speechreading in Deaf Adults with Cochlear Implants: Evidence for Perceptual Compensation - Pimperton, Hannah; Ralph-Lewis, Amelia; MacSweeney, Mairéad (Frontiers in Psychology, 2017)
Previous research has provided evidence for a speechreading advantage in congenitally deaf adults compared to hearing adults. A ‘perceptual compensation’ account of this finding proposes that prolonged early-onset deafness leads to a greater reliance on visual, as opposed to auditory, information when perceiving speech which in turn results in superior visual speech perception skills in deaf adults. In the current study we tested whether previous demonstrations of a speechreading advantage for profoundly congenitally deaf adults with hearing aids, or no amplificiation, were also apparent in adults with the same deafness profile but who have experienced greater access to the auditory elements of speech via a cochlear implant (CI). We also tested the prediction that, in line with the perceptual compensation account, receiving a CI at a later age is associated with superior speechreading skills due to later implanted individuals having experienced greater dependence on visual speech information. We designed a speechreading task in which participants viewed silent videos of 123 single words spoken by a model and were required to indicate which word they thought had been said via a free text response. We compared congenitally deaf adults who had received CIs in childhood or adolescence (N = 15) with a comparison group of hearing adults (N = 15) matched on age and education level. The adults with CI showed significantly better scores on the speechreading task than the hearing comparison group. Furthermore, within the group of adults with CI, there was a significant positive correlation between age at implantation and speechreading performance; earlier implantation was associated with lower speechreading scores. These results are both consistent with the hypothesis of perceptual compensation in the domain of speech perception, indicating that more prolonged dependence on visual speech information in speech perception may lead to improvements in the perception of visual speech. In addition our study provides metrics of the ‘speechreadability’ of 123 words produced in British English: one derived from hearing adults (N = 61) and one from deaf adults with CI (N = 15). Evidence for the validity of these ‘speechreadability’ metrics come from correlations with visual lexical competition data.